Deindustrialization, Gender, and Working-Class Militancy in Saint-Henri, Montréal - Burrill, Fred (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2023)
Tracing the history of gendered working-class responses to deindustrialization in the Montréal neighbourhood of Saint-Henri reveals that many of the local political initiatives of the 1960s and 1970s were connected to longer-term working-class efforts to navigate shifting patterns of capital accumulation extending back to the 1940s. The gendered tradition of territory-based organizing in this community encouraged women workers’ shop-floor militancy and was foundational for new forms of local political advocacy around issues like health care and housing. In deindustrialization’s moment, the concerns of a precariously employed, feminized working-class population spurred a crossover of industrial struggle with survival-focused reproductive labour issues, centred around a grassroots organization called the popir (Projet d’organisation populaire, d’information, et de regroupement). This pattern of gendered working-class militancy and solidarity persisted throughout the 1980s and shaped resistance to Saint-Henri’s subsequent gentrification at the turn of the new millennium.